إستخدام نسب الربحية في تقييم الحصة السوقية دراسة تحليلية لعينة من المصارف العراقية - حسن, زەمین دیار; قەرەداغی, كاوه محمد فرج (Sulaimani Journal for Humanities, 2021)
This study aims to study the correlation and impact relationship between the variable’s profitability ratios and the market share, and the problem of the study is to ask a question: Are profitability ratios used in assessing the market share in Iraqi commercial banks? The generally accepted financial indicators are used in the study which are return of equity, return on assets, net interest margin, and the return on deposits, as an independent variable, whose role is reflected in the respondent variable (market share) through each of the banking facilities provided to customers, total deposits, number of bank branches, number of employees, which are reflected in their final outcomes in their market value. The study covered a period extending from (2006-2019), and the study reached several conclusions, the most important of which is: The existence of the relationship and the significant statistical effect between the independent and approved variables, as the results of the analysis and comparison resulted in its negative presence in some banks indicating the lack of interest of the departments. From a scientific point of view, operating these indicators in its assessment of its market share. The study concluded with a set of recommendations that indicated the possibility of taking them into practice by those interested in the field of financial management and marketing of the banking system by increasing the number of its branches and the number of employees and increasing the type and number of banking facilities, especially the total deposits and granting loans.
Keywords: profitability ratios; market share